2021
DOI: 10.1097/grf.0000000000000611
|View full text |Cite
|
Sign up to set email alerts
|

Using Telehealth Approaches to Address Social Determinants of Health and Improve Pregnancy and Postpartum Outcomes

Abstract: Telehealth has expanded its reach significantly since its inception due to the advances in technology over the last few decades. Social determinants of health (SDOH) negatively impact the health of pregnant and postpartum women and need to be considered when deploying telehealth strategies. In this article, we describe telehealth modalities and their application to improve the SDOH that impact pregnancy and postpartum outcomes. Physicians and patients alike report satisfaction with telehealth as it improves ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Beyond the preoperative phase of care, the surgeon’s office should aim to ease access to postoperative care. Practice-wide enhancements such as a nurse-operated hotline for urgent questions and the availability of telehealth visits can potentially reduce unnecessary postoperative hospital use and ease the clinical burden for patients with limited social connections, transportation, and work-related time constraints 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the preoperative phase of care, the surgeon’s office should aim to ease access to postoperative care. Practice-wide enhancements such as a nurse-operated hotline for urgent questions and the availability of telehealth visits can potentially reduce unnecessary postoperative hospital use and ease the clinical burden for patients with limited social connections, transportation, and work-related time constraints 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In the wake of the COVID-19 pandemic, telehealth has become a necessary method of healthcare delivery. Telehealth has become a more viable option for the general population, and more specifically for hard to reach populations including new parents [136], under-resourced populations [137], and those facing mental health stigma. Social support has shown to have a significant impact on postpartum mental wellbeing, and isolation as a result of social distancing is a risk factor for developing postpartum depression [138].…”
Section: Alternative Methods Of Treatment Deliverymentioning
confidence: 99%
“…However, this study excluded women without access to a computer [ 91 ]. Studies from other settings have also reported improved access [ 48 , 72 , 92 , 93 ]. Conversely, Osarhiemen et al [ 94 ] identified that while telehealth did not mitigate inequities in access, it also did not widen existing disparities in the USA.…”
Section: Consumer Satisfactionmentioning
confidence: 99%